The COP9 signalosome complex regulates fungal development and virulence in the wheat scab fungus Fusarium graminearum - Chen, Ahai; Ren, Yiyi; Han, Xingmin; Liu, Chao; Zhou, Yifan; Xu, Chenghui; Qi, Hao; Ma, Zhonghua; Chen, Yun (Frontiers in Microbiology, 2023)
The COP9 signalosome (Csn) complex is an evolutionarily conserved complex that regulates various important cellular processes. However, the function of the Csn complex in pathogenic fungi remains elusive. Here, the distribution of Csn subunits in the fungal kingdom was surveyed, and their biological functions were systematically characterized in the fungal pathogen Fusarium graminearum, which is among the top 10 plant fungal pathogens. The results obtained from bioinformatic analyses suggested that the F. graminearum Csn complex consisted of seven subunits (Csn1-Csn7) and that Csn5 was the most conserved subunit across the fungi kingdom. Yeast two-hybrid assays demonstrated that the seven Csn subunits formed a complex in F. graminearum. The Csn complex was localized to both the nucleus and cytoplasm and necessary for hyphal growth, asexual and sexual development and stress response. Transcriptome profiling revealed that the Csn complex regulated the transcription abundance of TRI genes necessary for mycotoxin deoxynivalenol (DON) biosynthesis, subsequently regulating DON production to control fungal virulence. Collectively, the roles of the Csn complex in F. graminearum were comprehensively analyzed, providing new insights into the functions of the Csn complex in fungal virulence and suggesting that the complex may be a potential target for combating fungal diseases.